Mobile Marketing Training towards Increasing Business: A Case Study of Agri-Food Micro-Enterprises - Zakirah Othman; Nur Badriyah Kamarul Zaman; Noor Hidayah Abu; Syahida Abdullah; Emmy Farha Alias; Siti Jahroh (International Journal of Interactive Mobile Technologies (iJIM), 2024)
Mobile marketing (MM) refers to marketing through mobile platforms and has become a phenomenon in the business world. Many sectors utilize online applications for various business activities, including promotion and marketing. However, small and medium-sized enterprises (SMEs), especially those in the agricultural sector, face numerous challenges in using and determining training that is appropriate to their level of ability. Therefore, the objective of this study is to discuss the use of digital marketing training management (DMTM) by agri-food micro-enterprises in Peninsular Malaysia. A total of seventeen participants took part in this case study, and data were collected through surveys and semi-structured interviews between March 2022 and December 2022. The results led to the development of a DMTM model for agri-food micro-enterprises.